Allergic bronchopulmonary aspergillosis - Ritesh Agarwal (Indian Journal of Medical Research, 2020)
Allergic bronchopulmonary aspergillosis (ABPA) is an inflammatory disease caused by immunologic reactions initiated against Aspergillus fumigatus colonizing the airways of patients with asthma and cystic fibrosis. The common manifestations include treatment-resistant asthma, transient and fleeting pulmonary opacities and bronchiectasis. It is believed that globally there are about five million cases of ABPA, with India alone accounting for about 1.4 million cases. The occurrence of ABPA among asthmatic patients in special clinics may be as high as 13 per cent. Thus, a high degree of suspicion for ABPA should be entertained while treating a patient with bronchial asthma, particularly in specialized clinics. Early diagnosis and appropriate treatment can delay (or even prevent) the onset of bronchiectasis, which suggests that all patients of bronchial asthma should be screened for ABPA, especially in chest clinics. The current review summarizes the recent advances in the pathogenesis, diagnosis and management of ABPA.